Damage patterns in polyethylene fixed bearings of retrieved total ankle replacements. Issue 3 (April 2021) - Ho, Nathan C.; Park, Sang-Hyun; Campbell, Patricia; Van Citters, Douglas W.; Ebramzadeh, Edward; Sangiorgio, Sophia
Highlights: Semi-quantitative grading of burnishing, scratching, mechanical damage, pitting, and particles. Correlate the observed damage patterns with the in vivo kinematics of the ankle. Results indicate greater posterior aspect damage when compared to the anterior aspect. May indicate that the anterior to posterior motion of the talus throughout gait is being constrained. Abstract: Introduction: Poor long-term outcomes continue to hinder the universal adoption of total ankle replacements (TAR) for end stage arthritis. In the present study, polyethylene inserts of TARs retrieved at revision surgery were analyzed for burnishing, scratching, mechanical damage, pitting, and embedded particles. Methods: Fourteen retrieved polyethylene inserts from a fixed bearing total ankle replacement design currently in clinical use were analyzed. Duration of time in vivo was between 11.5 months and 120.1 months. Three investigators independently graded each articular surface in quadrants for five features of damage: burnishing, scratching, mechanical damage, pitting, and embedded particles. Results: No correlation was found for burnishing between the anterior and posterior aspects (p = 0.47); however, scratching and pitting were significantly higher on the posterior aspect compared to the anterior aspect (p < 0.03). There was a high correlation between burnishing and in vivo duration of the implant (anterior: R = 0.67, p = 0.01, posterior: R = 0.68, p = 0.01). Conclusion: The higher concentration of posterior damage on these polyethylene inserts suggested that prosthesis-related (design) or surgeon-related (technique) factors might restrict the articulation of the implant. The resulting higher stresses in the posterior articular surfaces may have contributed to the failure of retrieved implants Keywords: Retrieval, Polyethylene Damage, Total Ankle Replacement.